WEBBED MODEL INTEGRATED LEARNING ON PROBLEM SOLVING AND SELF- REGULATION SKILLS FOR PAUD STUDENT IN MOJOKERTO - Sutik, Sutik; Masitoh, Prof. Dr. Siti; Mariono, Dr. Andi (Srawung: Journal of Social Sciences and Humanities, 2022)
Early Childhood Education or commonly called PAUD is one of the formal educational institutions that presented at the pre-school level or before students register in kindergarten. This education presents activities that provide more and intense touch and affection, generally because at this time children have entered the "Golden Age" which has need for direct guidance by adults with basic activities through playing for students’ character development and learning motivation for children optimal growth. Webbed integrated learning model is one of the learning models developed at Pacet Mojokerto Kindergarten. This study shows how the influence of learning through conventional and integrated learning is associated with problem solving and self-regulation for kindergarten students at Pacet Mojokerto Kindergarten to 40 kindergarten students using quantitative methods with the assistance of SPSS type 22 Multi Variate analysis of variance (manova) to determine the effect of webbed model integrated learning on children's problem solving and self-regulation skills. From the research result, it was concluded that the Webbed Model Integrated Learning had a significant effect on increasing problem-solving and self- regulation abilities in early childhood education at the kindergarten level aged 5-6 years in the Pacet sub-district, Mojokerto.